The Role of Women in the Home Industry of Cassava Processing in Cireundeu Traditional Village - Kamila Nurul Faijah; Hasnatun Amaliyah; Rafa Sabila Putri Hidayat; Sri Damayanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study examines women's involvement in home industries as part of a strategy to meet family economic needs, particularly in indigenous communities that still maintain local cultural values. This study aims to analyze the role of women in the cassava processing home industry in the Cireundeu Traditional Village, including their involvement in the production process, their contribution to the family economy, and their role in maintaining local culture. The study used a qualitative approach with a descriptive design. Data were collected through in-depth semi-structured interviews, participant observation, and purposive selection of informants. The results show that women play a dominant role in processing cassava into various marketable products, such as opak (rice crackers), chips, and kecimpring (rice crackers). This involvement not only contributes to increasing family income through diversifying economic resources but also serves as a means of empowering women through the development of business skills and experience. In addition, women play a role in the cultural sustainability of the Cireundeu community through the preservation of traditional processing techniques and cassava-based products. Thus, women occupy a strategic position as economic actors and guardians of the cultural identity of indigenous communities.